Inhumanity, a heinous crime against health personnel in Pakistan: challenges and recommendations - Raja, Sandesh; Ali, Azzam; Adarsh raja (Journal of the Pakistan Medical Association, 2023)
Respected Sir, Violence is the utilization of actual power that either result in or has high possibilitys of causing injury, death, psychological mischief, or hardship. The World Health Organization estimates that physical violence affects 8–38 percent of healthcare employees at some time in their professional lives(1). An innumerable large number of health personals are verbally abused. Intolerance and hostility toward doctors are global phenomena. In1996, the Forty-Ninth World Health Assembly proclaimed violence as a significant public health issue(2). Violence is becoming more common in many professions, but it is known to be particularly prevalent in the medical area. Doctors have been the target of violence for a long time, as observed worldwide, and it is nothing new in Pakistan. In fact, because of the already common political violence and a fragile law enforcement system, countries like Pakistan are at a greater risk of violence. Exposure to violence in the medical fraternity consequences in accelerated tiers of anxiety, stress, insomnia, and depression which has a direct impact on the quality of treatment delivered to patients and can even end in a patient’s death. A cross-sectional study was carried out within the emergency departments of nine predominant tertiary hospitals in Pakistan, which revealed a significant problem, with nearly 77 per cent of physicians dealing with verbal or bodily abuse from patients and their attendants(3). According to the Pakistan Medical Association (PMA), An independent organization that addresses the problems of healthcare providers, 54 doctors were killed in Karachi between 2010 and 2014 for various reasons. Most incidents were reported in 2014, when approximately 17 doctors were killed(4). This is the only figure that is reported; many more go unreported. There are complicated motives in the back of the violence toward Health Care Personnel (HCP); as a result, medical disputes and, at times, violence have increased. However, the primary motives are poor medical service quality and communication between HCPs and patients. Inadequate security and funds can also lead to violence. Awareness campaigns to improve HCPs’ communication skills, better health care facilities, patient satisfaction, and attendants should be kept in the loop at every medical step, and security should be maintained in hospitals to protect the staff are among the preventative measures that can significantly reduce incidents of violence against HCPs.